(untitled) (Archaeologia Adriatica, 2025)
The paper presents examples of prehistoric olive fruit remains on the eastern Adriatic coast, from the Neolithic to the Iron Age. Physical remains of olive stones were unearthed at four prehistoric sites, three of which are now below sea level. The earliest known occurrence of olives is recorded in the Neolithic, while the beginning of olive cultivation on our coast has been proved to date to around 1400 BC, at the Turanj – Ričul site.